Marriage, maturity, choice: the Maria Hertogh story revisited - Nur Mufidah Binte Sapari (Nanyang Technological University, 2023)
When approaching the story of Maria Huberdina Hertogh, also known as Nadra, we are often led to themes of interracial marriages and colonial insensitivities that have been widely established in Singapore’s national narrative. Perhaps more interestingly, credits are often given to the English and Malay language press for sensationalising their coverage and triggering distress within the Muslim community. In an attempt to decentralise such ingrained narratives, this thesis calls for a reassessment of Malay language periodicals to unearth marginalised perspectives of the Malay-Muslim community during the Maria Hertogh tragedy. It looks at gender, in the words of Jeanne Boydston, as a “question of historical analysis” and argues that the episode reveals a complex “tug-of-power” between and within Muslim men and women regarding what defines maturity and the ideals of marriage. We will observe in this “tug-of-power” relationship the contrasting perceptions and expectations regarding the realm of childhood, adulthood, and matrimony. Viewed as a whole, more than an attempt to arouse Malay-Muslim feelings, Malay language periodicals brought to light the different voices against women and their bodies in post-war Singapore.